Evaluation of the Association Between Health State Utilities and Obesity in Sub-Saharan Africa: Evidence From World Health Organization Study on Global AGEing and Adult Health Wave 2 - Stella T. Lartey; Lei Si; Barbara de Graaff; Costan G. Magnussen; Hasnat Ahmad; Julie Campbell; Richard Berko Biritwum; Nadia Minicuci; Paul Kowal; Andrew J. Palmer (Elsevier Ltd, 2022)
Background:Obesity is a major public health challenge and its prevalence has increased across the age spectrum from 1980 todate in most parts of the world including sub-Saharan Africa. Studies that derive health state utilities (HSUs) stratified byweight status to support the conduct of economic evaluations and prioritization of cost-effective weight management in-terventions are lacking in sub-Saharan Africa.Objectives:To estimate age- and sex-specific HSUs for Ghana, along with HSUs by weight status. Associations between HSUsand overweight and obesity will be examined.Study Design:Cross-sectional survey of the Ghanaian population.Methods:Data were sourced from the World Health Organization Study of Global AGEing and Adult Health (WHO SAGE), 2014to 2015. Using a“judgment-based mapping”method, responses to items from the World Health Organization Quality-of-Life(WHOQOL-100) used in the WHO SAGE were mapped to EQ-5D-5L profiles, and the Zimbabwe value set was applied tocalculate HSUs. Poststratified sampling weights were applied to estimate mean HSUs, and a multivariable linear regressionmodel was used to examine associations between HSUs and overweight or obesity.Results:Responses from 3966 adults aged 18 to 110 years were analyzed. The mean (95% confidence interval) HSU was 0.856(95% CI: 0.850, 0.863) for the population, 0.866 (95% CI: 0.857, 0.875) for men, and 0.849 (95% CI: 0.841, 0.856) for women.Lower mean HSUs were observed for obese individuals and with older ages. Multivariable regression analysis showed thatHSUs were negatively associated with obesity (20.024; 95% CI:20.037,20.011), female sex (20.011; 95% CI:20.020,20.003),and older age groups in the population.Conclusions:The study provides HSUs by sex, age, and body mass index (BMI) categories for the Ghanaian population andexamines associations between HSU and high BMI. Obesity was negatively associated with health state utility in the pop-ulation. These data can be used in future economic evaluations for Ghana and sub-Saharan African populations.Keywords:health economic evaluations, health state utilities, obesity, sub-Saharan Africa, WHO SAGE Wave 2.